1993
DOI: 10.1002/gps.930080610
|View full text |Cite
|
Sign up to set email alerts
|

Physical assaults by psychogeriatric patients: Patient characteristics and implications for placement

Abstract: SUMMARYThe case notes of 137 patients admitted to a psychogeriatric assessment ward over 12 months were reviewed. The characteristics of patients who were assaultive prior to, or during admission were compared with those who were not. The reported prevalence of assaultive behaviour from the case notes was compared with that from the formal 'violent incident' forms. Twenty-three per cent of the patients had assaulted others prior to their admission, and 23% were assaultive during their admission. Those patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Few studies on aggression in the elderly have looked speci®cally at AD patients, but several have found that male dementia suerers are more likely to be assaultive than females (Burns et al, 1990;Eastley and Mian, 1993;Kalunian et al, 1990). There is no evidence to suggest that the disease process itself is dierent in men and women, so other factors must be relevant.…”
Section: Discussionmentioning
confidence: 96%
“…Few studies on aggression in the elderly have looked speci®cally at AD patients, but several have found that male dementia suerers are more likely to be assaultive than females (Burns et al, 1990;Eastley and Mian, 1993;Kalunian et al, 1990). There is no evidence to suggest that the disease process itself is dierent in men and women, so other factors must be relevant.…”
Section: Discussionmentioning
confidence: 96%
“…Aggressive behaviour in dementia is an important problem in the community (Ryden, 1988) as well as in institutions (Billig et al, 1991;Eastley and Mian, 1993). The number of intervention studies is increasing.…”
mentioning
confidence: 99%
“…Techniques to reduce this variability include careful coding (Zimmer et al, 1984), carefully de®ning every variable (Zimmer et al, 1984) and validation by positive correlation with scores on standardized scales (Eastley and Wilcock, 1997). Incident forms ®lled by sta may underestimate levels of aggressive behaviour (Lion et al, 1981;Eastley and Mian, 1993). Specially designed questionnaires or scales completed by sta or by informal carers often lack good data on their validity and reliability.…”
Section: Data Collectionmentioning
confidence: 98%
“…It causes considerable distress to relatives and carers (O'Connor et al, 1990;Everitt et al, 1991). It often results in poor receipt of domiciliary services (Shah, 1993), poor pain relief (Cariaga et al, 1991), referral to specialist services (Margo et al, 1980), long-term hospitalization (Shah, 1992;Eastley and Mian, 1993), nursing home placement (Steele et al, 1990), physical restraint (Guirguis and Durost, 1978) and overmedication (Shah, 1993;Martin et al, 1994). Thus, aggressive behaviour will be considered as à representative' and issues related to its measurement are discussed in detail; similar arguments can be rehearsed for other forms of behaviour disturbances.…”
mentioning
confidence: 99%